Formaldehyde Content in Indonesian Food and the Analysis Method: A Review - Putri, Anggita Rosiana; Awidarta, Kevin; Pratita Ihsan, Bachtiar Rifai; Khaerunisa, Intan; Ulum, Muhammad Bachrul; Huda, Laili Fadhotun (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Apart from being rich in culture, Indonesia is also rich in food culture. However, in some cases, there are illegal additions of formalin (37% formaldehyde) to food to extend shelf life. If humans consume food containing formaldehyde, it will have a harmful impact. Formaldehyde has the potential to cause cancer. In recent years, formaldehyde has still been found in several Indonesian foods. There are several analytical methods developed to detect formaldehyde levels in food. This review overview of the formaldehyde effect to human health, formaldehyde content in fish and Indonesian food, and the detection methods.